Commercial Agriculture and Rural Development: Evidence from the Zimbabwe Farm Project in Tsonga, Nigeria - Olawepo, R. A. (Asian Journal of Agriculture and Rural Development, 2012)
When the Zimbabwe Farmers were brought to Kwara State, Nigeria in 2004, the intention of the government was to enable the local farmers benefit from their wealth of experience through commercial farming especially in the area of grain production in Tsonga and its environment. Six years after continuous farming, a survey evaluation was done through sampling of 240 farmers within their environment. Results showed that about 20% of the labour force required by the Zimbabwe farmers was obtained within the local environment and most people were employed as labourers, security guards and other unskilled labours. Similarly 3% of the local farmers were also trained to improve local productions while 18.8% of the farmers observed increased productivity and subsequent increase of income as a result of the commercial activities of these new farmers. Apart from these, the state of rural infrastructures like roads, electricity and potable water supplies were improved upon jointly by the State government and the Zimbabwe farmers. Local production of milk, rice, poultry, soya beans and animal fields for international markets were introduced. This has also affected local market organization in the locality positively. Even though some challenges were identified by local farmers, appropriate recommendations were presented accordingly.